Salafis, salafism and modern salafism: what lies behind a term? - Mohamed Bin Ali (2016)
The use of the term Salafi and Salafism in the contemporary period is ambiguous and in many ways confusing. The pivotal question of who or what group qualifies as Salafi remains in dispute. What is Salafism and who are the Muslims referred to as Salafis?